KEPEMILIKAN TANAMAN PADA TANAH PINJAMAN MENURUT FIQH MUAMALAH (Studi kasus di Jorong Guguak Baruah, Padang Magek) - Asep Wendy; Afrian Raus (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the ownership status of plants and land in the loan agreement ('ariyah) in Jorong Guguak Baruah Nagari Padang Magek according to Fiqh Muamalah. The problem is that the implementation of borrowing loans ('ariyah) is not in accordance with the initial agreement, namely to plant chilies, but in practice the borrower plants papaya and banana trees, at the initial agreement the loan limit is until the land is needed back by the lender, but in practice the borrower Instead, they asked for compensation and continued to use the land until the time limit specified in the initial agreement of the two parties. From this problem arose the question of how the status of land ownership in the loan agreement ('ariyah) was located in Jorong Guguak Baruah Nagari Padang Magek and how the legal consequences of the plants in the loan agreement ('ariyah) in Jorong Guguak Baruah Nagari Padang Magek according to Fiqh Muamalah. This research is a field research (field research). The data were obtained through interviews and observations. This study found that the status of land ownership in the loan agreement ('ariyah) in Jorong Guguak Baruah Nagari Padang Magek is fully owned by the lender with proof of land certificate in the name of the lender and a letter of sale and purchase of land. The status of the ownership of the plant is owned by the borrower until the agreed time limit.. The legal consequences of the plant in the loan agreement ('ariyah) in Jorong Guguak Baruah.